The first record of the genus Gracilidris (Hymenoptera: Formicidae: Dolichoderinae) from Colombia - GUERRERO, ROBERTO J.; SANABRIA, CATALINA (Revista Colombiana de Entomología, 2011)
The dolichoderine ant genus Gracilidris and its sole species, G. pombero, are recorded for the first time for Colombia from populations from the foothills of the Colombian Amazon basin. Comments and hypotheses about the biogeography of the genus are discussed.